Decreasing the Dose to the Rectal Wall by Using a Rectal Retractor during Radiotherapy of Prostate Cancer: A Comparative Treatment Planning Study. (4th June 2014) - Nilsson, Kristina; Johansson, Andreas K.; Montelius, Anders; Turesson, Ingela; Heikkinen, Risto O.; Ljung, Gunilla; Isacsson, Ulf
Abstract : Aim . The aim of the study was to examine the dosimetric effect of rectal retraction, using a rectal retractor, by performing a comparative treatment planning study. Material and Methods . Treatment plans using volumetric arc therapy (VMAT) were produced for ten patients both with and without rectal retraction. A hypofractionation scheme of 42.7 Gy in seven fractions was used. The dose to the rectal wall was evaluated for both methods (with and without retraction) using four dose-volume criteria:V 40.1  Gy, V 38.3  Gy, V 36.5  Gy, andV 32.6  Gy . Results . The retraction of the rectal wall increased the distance between the rectal wall and the prostate. The rectal wall volume was reduced to zero for all dose-volume values except forV 32.6  Gy, which was 0.2 cm 3 in average when the rectal retractor was used. Conclusion . There was a significant decrease ofV 40.1  Gy, V 38.3  Gy, V 36.5  Gy, andV 32.6  Gy when the rectal retractor was used without compromising the dose coverage of planning target volume (PTV).